2018
DOI: 10.1007/s11222-018-9820-8
|View full text |Cite
|
Sign up to set email alerts
|

Long memory estimation for complex-valued time series

Abstract: Long memory has been observed for time series across a multitude of fields, and the accurate estimation of such dependence, for example via the Hurst exponent, is crucial for the modelling and prediction of many dynamic systems of interest. Many physical processes (such as wind data) are more naturally expressed as a complex-valued time series to represent magnitude and phase information (wind speed and direction). With data collection ubiquitously unreliable, irregular sampling or missingness is also commonpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…In Figure 2 we display the kernel density estimate plots of the deviation of the parameter estimates for each parameter (relative to its true value) using (17) and ω ∈ [−π, π] (i.e. the second row of Table 2).…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 2 we display the kernel density estimate plots of the deviation of the parameter estimates for each parameter (relative to its true value) using (17) and ω ∈ [−π, π] (i.e. the second row of Table 2).…”
Section: Simulation Studymentioning
confidence: 99%
“…Complex-valued representations of bivariate time series are widely used in statistics [17,40,42], signal processing [30,34], and numerous application disciplines [2,13,43]. A key advantage of the complex-valued representation is that it can be conveniently used to separate structures in coupled bivariate time series that are circular or noncircular when viewed in the complex plane.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Opałka et al [26] demonstrated that a more accurate RUL prediction can be achieved by dividing time series sensor data into smaller segments according to a certain indicator. The Hurst exponent, which was developed by Hurst (1900Hurst ( -1978 based on the rescaled range (R/S) analysis method, has been extensively applied to determine the long-term memory of time series data that are varying in degree and time span [17]. There are increasing uses of the Hurst exponents in signal segmentation to support different applications [12,25].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, (15) implies Rzz should be a zero-matrix for any given α to satisfy circularly symmetry. Thus, circularity implies properness whereas the converse is not true in general.…”
Section: ) Complex Random Vectorsmentioning
confidence: 99%